Cyprus: Behind closed (journalistic) doors - Eberwein, Tobias; Fengler, Susanne; Karmasin, Matthias (My University, 2017)
This chapter maps the status of media accountability in the Republic of Cyprus, examining the instruments of media accountability used by the Cypriot media in terms of their structural features as well as their journalistic content. Although in Cyprus the key traditional institutions of accountability seem to be in place, effective mechanisms for transparency are lacking, due to deep-rooted structures that have prevented the development of autonomous media organizations. Cypriot journalists have managed to develop an independent body for self-regulation, but they neglected to efficiently incorporate media audiences and develop a culture of open interaction with the public, creating the sense that it is a process taking place behind closed (journalistic) doors. At the same time, the public has not yet utilized the available digital tools to take up the role of the ‘media watchdog’.